Scenario Forecast for Wind Turbine Manufacturing in Russia - Ratner, Svetlana Valerievna; Klochkov, Vladislav Valerievich (International Journal of Energy Economics and Policy, 2017)
In this paper we suggest a method of evaluation of the prospects of creating and developing a wind energy-engineering sector in Russia, which is oriented, primarily, on domestic needs. Using the concept of learning curves as a framework, we evaluate the possible volumes of production of green energy equipment in Russia and prospects of competitiveness of such industries. Analysis of documents which determine the future development of Russian energy shows market share of Russian manufactures will be significantly lower than that of most wind energy equipment manufacturers, and wouldn’t allow for a competitive level of costs and prices of Russian wind energy equipment. In the initial stages of domestic development of wind energy equipment, the average labor productivity may make up around 70-90% of the level of worldwide leaders, however this loss in productivity can be offset by tax benefits, which would stimulate entrepreneurs to localize their productions in Russia. Keywords: energy equipment machine-building, productivity, learning-by-doing effect JEL Classifications: O33, Q42, Q47, Q48